The digital-mediated extensive reading on English Language learning of agriculture students - Prasetianto, Mushoffan; Maharddhika, Rizkiana; Trimus, Syakilla Eka Putri Lestari (Intelektual Pustaka Media Utama, 2024)
Reading is a skill that is initially taught in schools. Students are introduced to the alphabet and later learn to read texts. Reading Foreign languages is also introduced when students learn a foreign language. The student requires reading activities that include vocabulary learning. Extensive reading is one of the practical activities of reading. Nowadays, extensive reading activities include reading printed and digital text in e-books, journals, and internet and social media articles. In addition, digital extensive reading research on university students of agriculture is still rare. Thus, research on digital-mediated extensive reading in agricultural students’ needs to be conducted to investigate whether it improves their reading comprehension. This study involved 84 agricultural students majoring Agroecotechnology study program. The participants take an English course. The data for this study was taken from the pre-test and post-test scores and questionnaire. The data will be analyzed using descriptive and inferential statistics. The results of the study shows that the digital-mediated extensive reading effectively enhances the student's reading comprehension in English as academic purposes (EAP) setting, and the students express that the digital-mediated extensive reading provides flexibility, technology utilization, and reading.